Solvent-free, slow-curing, and corrosion-resistant flame retardant polyurea enabled by a Schiff base latent curing agent and phosphate polyol - Yun-Cheng Zhao; Xing-Yu Wang; Ke Shang; Bin Zhao (Polymer Testing)
Polyurea (PUA) is widely recognized for its excellent waterproofing and impact resistance, making it a popular choice for protective coatings. However, its inherent flammability and rapid reaction kinetics pose significant challenges for both fire safety and processing. In this study, a Schiff base latent curing agent (D2000-MIBK) and a phosphate-containing polyol (OP550) were employed to develop a solvent-free, intrinsically flame-retardant, slow-curing PUA. The incorporation of D2000-MIBK effectively moderated the curing process, addressing the rapid reaction typical of conventional PUA systems, while OP550 significantly improved flame retardancy and mechanical performance. At just 2.22 wt%, OP550 enabled PUA-2 to achieve a UL-94 V-0 rating, demonstrating self-extinguishing behavior and reduced flaming drips. Thermogravimetric analysis confirmed that OP550 promoted char formation without altering the thermal decomposition profile of PUA, while dynamic mechanical analysis showed increased stiffness with negligible impact on the glass transition temperature. PUA-2 exhibited exceptional mechanical properties, including a tensile strength of 15.4 MPa, elongation at break of 1287.5 %, and tearing strength of 65.4 N mm−1, as well as excellent resistance to acidic, alkaline, and saline environments. Atomic force microscopy revealed optimized microphase-separated morphology, enhancing interfacial interactions and contributing to improved toughness and flexibility. This study introduces a novel strategy for developing high-performance PUA materials with superior flame retardancy, mechanical robustness, and controllable curing, offering significant potential for applications in protective coatings and structural components under demanding conditions.